Responsible tourism and hospitality: The intersection of altruistic values, human emotions, and corporate social responsibility - Naveed Ahmad; Aqeel Ahmad; Irfan Siddique (Administrative Sciences, 2023)
The burgeoning tourism and hospitality industry is plagued by numerous challenges that pose significant hurdles to its long-term success and sustainability. These challenges encompass a range of factors, including fierce competitive convergence, rapid obsolescence of innovative strategies, and the relentless pursuit of ever-greater competitiveness in the marketplace. In such a service-oriented industry, where customer satisfaction is the sine qua non of success, the role of corporate social responsibility (CSR) in shaping consumer attitudes and behavior cannot be overstated. Despite this, the empirical evidence on the impact of CSR on brand advocacy behavior among hospitality consumers (BADB) remains somewhat underdeveloped and incomplete. In light of this knowledge gap, the basic objective of our study is to examine the complex interplay between CSR and BADB in the context of a developing country's hospitality sector. The authors place a particular emphasis on the mediating role of consumer emotions and the moderating influence of altruistic values (ALVS) in shaping this relationship. Through rigorous empirical analysis, the authors demonstrate that CSR positively and significantly impacts BADB, with consumer engagement (CENG) serving as a crucial mediating variable that facilitates this relationship. These findings have significant theoretical and practical implications for the tourism and hospitality industry. Specifically, the authors show that the judicious deployment of CSR initiatives in a hospitality context can foster a positive behavioral psychology among consumers and, in turn, enhance their advocacy intentions towards the brand. This underscores the importance of carefully crafted CSR strategies to secure a competitive advantage in this dynamic and rapidly evolving sector.
Keywords: 350; advocacy intentions; altruism; behavioral psychology; corporate social responsibility; human emotions; tourism and hospitality